1997
DOI: 10.1046/j.1365-313x.1997.11020263.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repression by Oshox1, a novel homeodomain leucine zipper protein from rice

Abstract: This paper describes the characterization of Oshox1, a cDNA clone from rice encoding a member of the homeodomain-leucine zipper (HD-Zip) class of putative transcription factors. Oshox1 maps to chromosome 10 and belongs to a family of related rice genes. Two-hybrid assays showed that Oshox1 protein can homodimerize, but can also form heterodimers with an Arabidopsis HD-Zip protein. This suggests that protein-protein interactions may also occur between different HD-Zip proteins in rice, which would provide enorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 0 publications
4
94
0
Order By: Relevance
“…Nuclear localization of the GFP-tagged proteins was confirmed by overlapping signal with a nucleic acid stain (DAPI). N-terminally GFP-tagged rice Oshox1 (Meijer et al, 1997), a different type of homeodomain protein, was used for comparison. In contrast to the partial nuclear localization pattern of the GFP-tagged KNOX proteins, GFP-tagged Oshox1 protein localized exclusively to the nucleus (n ÂŒ 286, Figure 1E).…”
Section: Localization Of Gfp-tagged Knox Proteins In Transient Assaysmentioning
confidence: 99%
“…Nuclear localization of the GFP-tagged proteins was confirmed by overlapping signal with a nucleic acid stain (DAPI). N-terminally GFP-tagged rice Oshox1 (Meijer et al, 1997), a different type of homeodomain protein, was used for comparison. In contrast to the partial nuclear localization pattern of the GFP-tagged KNOX proteins, GFP-tagged Oshox1 protein localized exclusively to the nucleus (n ÂŒ 286, Figure 1E).…”
Section: Localization Of Gfp-tagged Knox Proteins In Transient Assaysmentioning
confidence: 99%
“…In vitro and in vivo binding assays have demonstrated that HDZip proteins from Arabidopsis, C. plantagineum and rice preferentially bind to two 9-bp pseudopalindromic sequences, CAA-T(A/T)ATTG (HDE1) and CAAT(G/C)ATTG (HDE2) (Frank et al, 1998;Meijer et al, 2000;Johannesson et al, 2001;Deng et al, 2002). Furthermore, different HDZip factors were shown to act either as repressors or as activators of HDEcontaining synthetic reporter genes (Meijer et al 1997;Ohgishi et al 2001). Autoregulation through HDE sites in their own promoters was demonstrated for the Arabidopsis HDZips, ATHB2 and ATHB6 (Ohgishi et al, 2001;Himmelbach et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These signal transduction networks are related to the general growth regulation of plants. The overexpression of sense or antisense HD-Zip I or II mRNA usually alters the growth rate and development of a plant (Schena et al, 1993;Aoyama et al, 1995;Meijer et al, 1997). Most members of the HD-Zip III subfamily play roles in cell differentiation in the stele (Baima et al, 1995;Zhong and Ye, 1999).…”
Section: Introductionmentioning
confidence: 99%